Fertility Improvement Following Herbal Treatment in Subfertile Buffalo Bulls - Kumar, Ajeet; Shivkumar,; Bisla, Amarjeet; Singh, Ashwani Kumar; Honparkhe, Mrigank; Dhindsa , Shahbaz Singh (The Indian Journal of Animal Reproduction, 2022)
The present experiment was conducted to study the impact of herbal treatment on post thaw semen quality and fertility in subfertile buffalo bulls. Three Murrah subfertile buffalo bulls maintained at bull station, Guru Angad Dev Veterinary and Animal Sciences University (GADVASU), Ludhiana, India (Latitude/Longitude, 30.55°N, 75.54° E) with the history of poor semen quality (pre-freeze individual motility < 60%, post-thaw individual motility < 40%, Viability < 70% and Abnormality > 20%) were orally supplemented with herbal mixture (Panax ginseng roots, Shilajit, Withania somnifera roots, Tribulus terrestris fruits, Turnera diffusa leaves, Ptychopetalum olacoides  bark of each 400 mg/100 kg body weight and 300 mg/100 kg body weight of Pausinystalia yohimbe bark) daily for 60 days of treatment phase. Two semen ejaculates per week per bull were collected during pre-treatment, treatment and post-treatment phases of 60 days each and extended with Tris egg yolk extender. The freezing of extended semen was carried out in a biofreezer (4°C to -15°C @-30°C/min, -15°C to -140°C @-50°C/min) followed by plunging into liquid nitrogen for storage. Post thaw semen quality was assessed in terms of individual motility, viability, total sperm abnormalities. Present study revealed that the oral treatment of subfertile buffalo bulls with Panax ginseng roots, Shilajit, Withania somnifera roots, Tribulus terrestris fruits, Turnera diffusa leaves; Ptychopetalum olacoides bark each @ 400 mg/100 kg body weight and Pausinystalia yohimbe bark @ 300 mg/100 kg body weight for 60 days improved post thaw semen quality and fertility.
Keywords: Bull; Semen; Libido; Herbal; Subfertility